Study of the effect of different concentrations of salicylic acid against Pseudomonas savastanoi pv. savastanoi causal agent of olive knot disease in vitro - احمد رواد; موسى السمارة; ابراهيم العبيد; إياد محمد (Latakia University Journal -Biological Sciences Series, 2023)
This research aimed to study the efficiency of salicylic acid at different concentrations against the bacteria Pseudomonas savastanoi pv. savastanoi that causes olive knot disease in vitro. Pathogenic bacteria were isolated from galls on infected olive trees in kadmous area (Tartous Governorate, Syria). They were grown on Nutrient agar (NA) medium, and the inhibitory effect of salicylic acid was tested by diffusion method, that depends on placing paper discs with limited concentrations of salicylic acid on the surface of the medium cultured by the isolate and incubating at 28 °C for 48 hours, then measuring the diameter of the Inhibition distance around the paper disc treated with salicylic acid in its different concentrations. The results showed that salicylic acid at different concentrations approved (0.5,0.75,1,2) mmol an inhibitory effect on the growth of Pseudomonas savastanoi pv. savastanoi and the values ​​were (0,14.4,24.4,28)%, respectively. The results of this research showed that salicylic acid is an important natural source that can be used to control of the bacteria that cause olive knot disease in the future.